The effect of amygdala kindling on neuronal firing patterns in the lateral thalamus in the GAERS model of absence epilepsy - ONAT, FİLİZ (WILEY, 2014)
ObjectiveThe co-occurrence of absence and mesial temporal lobe epilepsy is rare in both humans and animal models. Consistent with this, rat models of absence epilepsy, including genetic absence epilepsy rats from Strasbourg (GAERS), are resistant to experimental temporal lobe epileptogenesis, in particular by amygdala kindling. Structures within the cortical-thalamocortical system are critically involved in the generation and maintenance of the electrographic spike-and-wave discharges (SWDs) that characterize absence seizures. Using in vivo electrophysiologic recordings, this study investigated the role of thalamocortical circuitry in the generalization of amygdala-kindling induced seizures in the GAERS and the nonepileptic control (NEC) strain of Wistar rats. MethodsGAERS and NEC rats were implanted with a stimulating electrode in amygdala and stimulated at afterdischarge threshold twice daily to a maximum number of 30 stimulations. Thereafter extracellular single neuron recordings were performed in vivo under neuroleptanesthesia in the thalamocortical network. ResultsIn NEC rats, amygdala kindling induced convulsive class V seizures and altered characteristics of neuronal activity in the thalamic reticular nucleus (TRN), in particular decreased firing rates and increased burst firing patterns. Less marked changes were seen in other regions examined: the ventroposteromedial nucleus of thalamus (VPM), the CA3 region of the hippocampus, and the deep layers (V/VI) of the cortex. GAERS did not progress beyond class II seizures, with a matched number of kindling stimulations, and the thalamic neuronal firing alterations observed in NEC rats were not seen. SignificanceThese data suggest that the TRN plays an important role in kindling resistance in GAERS and is central to the control of secondary generalization of limbic seizures. A PowerPoint slide summarizing this article is available for download in the Supporting Information section .
Keywords: Amygdala kindling; Absence epilepsy; Ventrobasal thalamic nucleus; In vivo juxtacellular single unit recordings; Mesial temporal lobe epilepsy; WAVE DISCHARGES; TEMPORAL-LOBE; RAT MODEL; ELECTRICAL-STIMULATION; NEURAL INFORMATION; RETICULAR NUCLEUS; SPONTANEOUS SPIKE; LESION PLACEMENT; SEIZURES; RESISTANCE